Adipose tissue and sustainable development: a connection that needs protection - Tremblay, Angelo; Picard-Deland, Éliane; Panahi, Shirin; Marette, André (Frontiers in Pharmacology, 2015)
Obesity is generally considered as an excess body fat that increases the risk to develop ergonomic, metabolic and psychosocial problems. As suggested in this paper, body fat gain is also a protective adaptation that prevents body lipotoxicity, contributes to the secretion of molecules involved in metabolic regulation, and dilutes lipid soluble persistent organic pollutants (POPs). Recent literature shows that this protective role of adipose tissue is more solicited in a modern context in which unsuspected factors can affect energy balance to a much greater extent than what is generally perceived by health care professionals. These factors include short sleep duration, demanding mental work, and chemical pollution whose impact is more detectable in a context dominated by economic productivity and competitiveness. Since these factors might also include the increase in atmospheric CO2, it is likely that obesity prevention will need the support of a promotion in sustainable development, whether it is for human health and well-being or global ecological protection.